A Multidimensional Predictive Model of Loneliness in Indonesian Generation Z - Siti Mahmudah; Salami Mahmud; Dian Mufitasari; Fuji Astutik; Umdatul Khoirot (SCAD Independent, 2026)
Loneliness among Generation Z has become a pressing public health issue, reflecting the paradox of increasing isolation despite high digital connectivity. This study aimed to test a multidimensional model integrating psychological, social, and spiritual factors to explain loneliness, with social support examined as a key mediating mechanism. Employing a quantitative cross-sectional design, data were collected from 527 Indonesian Generation Z participants using validated instruments, and analyzed through GSCA-SEM and path analysis with JASP. The findings revealed that self-compassion (β = -0.005, p = 0.015) and self-acceptance (β = -0.006, p = 0.007) directly reduced loneliness, while gratitude unexpectedly exhibited a positive association (β = 0.015, p = 0.005). Social support significantly mediated the influence of both social interaction (β = -0.037, p < 0.001) and self-compassion (β = -0.040, p < 0.001), explaining 54.7% of the variance (GFI = 0.947). These results challenge conventional theories, demonstrating that gratitude may operate differently in digital-native contexts and highlighting the central role of social support in translating interaction and psychological resources into reduced loneliness. The study offers theoretical innovation by proposing an integrated framework of loneliness and provides practical implications for developing culturally sensitive interventions for Generation Z in the digital era.